Social prescribing of nature therapy for adults with mental illness living in the community: A scoping review of peer-reviewed international evidence - Thomas, Tamsin; Aggar, Christina; Baker, James; Massey, Debbie; Thomas, Megan; D’Appio, Daniel; Brymer, Eric (Frontiers in Psychology, 2022)
Social prescribing of nature therapy ‘green social prescribing’ facilitates access to local nature-based activities that improve biopsychosocial wellbeing outcomes, are affordable, accessible, and can be adapted to context. These are becoming increasingly popular and grey literature is emerging, however peer-reviewed scientific evidence is exiguous. This scoping review aimed to identify and critique peer-reviewed evidence for green social prescribing interventions and develop recommendations for research and clinical practice. Included studies were published in peer-reviewed journals in English on/after 1 January 2000. Participants were community-living adults with mental illness; Intervention was any green social prescribing program; Comparator was not restricted/required; Outcomes were any biopsychosocial measures; and any/all Study Designs were included. Twelve databases were searched on 15 October 2022; these were Academic Search Premier, APA PsycArticles, APA PsycINFO, CINAHL, Cochrane Library, Google Scholar, JSTOR, ProQuest, PubMed, Science Direct, Scopus, and Web of Science. The Mixed Methods Appraisal Tool was used to assess quality. Seven publications describing 6 unique studies (5 UK, 1 Australia) were identified including 3 mixed-methods, 2 qualitative, and 1 RCT. Participants included 334 adults (45% female, aged 35-70 years); sample sizes ranged from 9-164. All studies showed improvements in biopsychosocial wellbeing, and participants from most studies (n=5) reported increased connection to the earth and intention to further access nature. Participant demographics and diagnoses were poorly reported, and intervention activities and assessments varied considerably. However, MMAT scores were good overall suggesting these studies may reliably demonstrate intervention outcomes. We conclude that socially prescribed nature therapy can improve biopsychosocial wellbeing and is a potentially important intervention for mental illness. Recommendations for research and clinical practice are provided.